Long term changes in voting power and control structure following the unification of dual class shares - Beni Lauterbach; Yishay Yafeh (Fondazione Eni Enrico Mattei (FEEM), 2009)
We follow the evolution of ownership structure in a sample of 80 Israeli companies that unified their dual-class shares in the 1990s, and compare it with a control sample of firms that maintained their dual share structure at least until 2000. Our main findings are as follows. First, controlling shareholders offset the dilution of voting rights they incurred upon unification by: 1) increasing their holdings prior to the unification (ex-ante preparation), and 2) by buying shares afterwards; by the end of the sample period their voting power was only marginally lower than in the control sample. This suggests that marginal voting rights are important to controlling shareholders even beyond the 50% threshold. Second, share unifications were not associated with much change in the identity of controlling shareholders. Third, the proportion of firms affiliated with pyramidal business groups in the sample of unifying firms was lower than in the population of listed firms as a whole and not different from that in the control sample, suggesting that pyramidal ownership structures did not replace dual class shares. Finally, unifying firms did not exhibit a substantial improvement in their performance and valuation in comparison with the control sample. We conclude that the regulatory attempt to enforce one share-one vote yielded, at best, a minor improvement in corporate governance.
Keywords: G30; G32; 330; Dual class shares; corporate governance; Corporate Governance; Eigentümerstruktur; Aktienstimmrecht; Israel